How do Militant Organizations Respond to Counterterrorism? Introducing the LIVE Typology, with Examples from Proscription in Pakistan - Feyyaz, Muhammad (Terrorism and political violence, 2026)
How do militant organizations respond to counterterrorism? A vast literature seeks to understand the effects of counterterrorism, examining outcomes such as levels of violence. However, violence is only one way that militant groups can respond to pressure. We focus on terrorist designation or proscription, the sanctions many states and international organizations impose on militants as an attempt to weaken them. We introduce a new typology of armed group responses to counterterrorism: (L)egal tactics like lawsuits or petitions, (I)dentity shifts like name changes or fragmentation, (V)iolence increases or decreases, and (E)conomic or financial tactics such as changing funding sources. These four approaches can be summarized by the acronym LIVE. Empirically, we illustrate the model with examples from the case of militant organizations in Pakistan, an important and under-studied case. Overall, the LIVE typology can be helpful for anticipating the repertoire of responses to counterterrorism, and for explaining armed group behavior generally.